THE EFFECTIVENESS OF THE TREATMENT OF Pinus halepensis Mill. SEEDS ULTRASONIC IRRADIATION AND GIBBERELLIC ACID IN SOME PHYSIOLOGICAL CHARACTERISTICS IN SUBSEQUENT SHOOTS - Mudhafar Abdullah; Zuhair A. Dawood; Sabah Gazi Shareef (Mesopotamia Journal of Agriculture)
The results of the chemical analysis showed that the values ​​of each of the leaves content of the Pinus halepensis Mill. seedlings of the total phenols and chlorophyll total and potassium have increased significantly when treating the seeds by 20 kHz ultrasound waves in comparison to that of 40 kHz. from these results of the chemical analysis. one can note that all periods of ultrasound waves caused a significant increase in the leaves content of the total carbohydrates. potassium and calcium compared to control treatment. the findings suggest that the treatment of seed immersion with Gibberellic acid solution at 100 and 200 mg. L-1 concentrations led to a significant increase in the leaves content of the total protein. while a 200 mg. L-1 concentration caused a significant increase in the leaves content of carbohydrates and total phenols in comparison to control treatment. A 100 mg. L-1 concentration led to a significant increase in the leaves content of potassium in comparison to control treatment.